A atuação miliciana nas chacinas e o direito penal do inimigo - SOUZA, Marcielly Cristiny Monteiro de (2022)
Given the advances in the actions of criminal organizations, death squads and militias, research on this topic is necessary. With such relevance, it is also essential to study the theory called Criminal Law of the Enemy which manifests itself in the roots of punitive power. The present research aims to study the correlation of the Criminal Law of the Enemy with the militia action in the massacre that took place in the city of Belém do Pará, in November, 2014. This action took place in retaliation for the murder of Cabo PM Marco Antônio Figueiredo, resulting in ten deaths distributed in the neighborhoods of Guamá, Terra Firme, Canudos, Marco, Jurunas and Tapanã. For the research, it is necessary to have a discussion that goes through the conceptualization and differentiation of the terms extermination groups and militias, as well as the exposition of the laws that deal with this topic. After that, this discussion will be applied to the reality of the militia's criminal organization's performance in the city of Belém showing the characteristics of this manifestation. It appears that through the Criminal Law of the Enemy, the modus operandi of the militias is addressed to at the peripheral population, where the main target is the young black people, as can be seen in some massacres, such as the massacre that happened in November 2014.